STRENGTH OF REINFORCED CONCRETE DOUBLE CANTILEVER BRIDGE PIERHEAD – NUMERICAL STUDY STRUT – AND – TIE - METHOD (STM) SNI 2847:2019 - Fery Riswanto; Pariatmono Sukamdo (Jurnal Infrastruktur, 2023)
Shear stress in the double cantilever bridge pierhead due to geometric discontinuity and load transferred from girder to column have a potentially diagonal crack in the structure. Strut-and-Tie Method (STM) is suitable to design pierheads that resist large shear stress (Piscesa & Tavio, 2020). Today, STM provision has developed with rectangular deep beams (Varney et al., 2015). To expand the application of STM, knowing the behavior of a double cantilever bridge while transferring load, must be verified. The goal of this research is to verify the feasibility of STM SNI 2847:2019 chapter 23 to predict the strength. The structure has been designed using SNI 2847:2019 with 3 specimens (S1-0.3-1; S1-0.4-1.2; S1-0.5-1.5). To find the truss system in the STM using BESO2D programs. The truss system output is analyzed with ETABS. Knowing nominal capacity design with the provision STM SNI 2847:2019. Then investigated ultimate performance used Finite Element Method, FEM software (Abaqus). The finding result is (1) load distribution of each specimen was confirmed same between STM and FEM. (2) Strength ratio, in the specimens respectively at 1.118; 1.09; 1.293, with more than 1 mean design using STM is conservative. (3) Deflection occurs respectively at 12.88mm; 7.96mm; 2.048mm (allowable limit is 18.75mm).